Constructivist theory and its aplication to the teaching of grammar in the ESL classroom: teaching the possessive case of nouns, prepositions, adverbs of frequency, first and second conditional, will present, would, past - Inga, Paola; Tapia, Soledad
During the teaching - learning process we have faced as students and teachers different kinds of difficulties when learning a new language, especially with grammar because teachers think that memorizing is the best way of learning a structure. There are different kinds of methodologies to teach English.That´s why we have focused this thesis on the Constructivist theory that is a view of learning based on the belief that knowledge isn´t a thing that can be simply given by the teacher at the front of the room to students in their desks. Rather, knowledge is constructed by learners through an active, mental process of development; learners are the builders and creators of meaning and knowledge. We have developed four units based on possessive case of nouns, prepositions, adverbs of frequency, first and second conditional using this theory, which have different activities for each grammar point; each unit has a real life situation that let students practice more. The teacher provides students with experiences that allow them to predict, manipulate objects, pose questions, research, imagine, and invent. Finally, we provide an application test for each unit; they can be modified according to the necessities of students and teachers. We have to remember that with this theory students are evaluated during the whole process and not only at the end of it. We hope that this thesis may help teachers change their traditional way of teaching using this theory improving the teaching-learning process